The Impact of Financial Performance on Stock Prices in Companies in the Property and Real Estate Sector - Dara Ayu Nianty (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2023)
The purpose of this research is to assess the impact of financial performance on stock prices for property and real estate sector companies trading on the Indonesia Stock Exchange between 2018 and 2020. The stock price is the independent variable in this analysis, while the current ratio (CR), return on assets (ROA), and debt to equity ratio (DER) are the financial ratios used to evaluate the company's performance. The Indonesia Stock Exchange served as the focus of this investigation. Tertiary sources are mined for information. There were 30 participants in total, 10 of which were businesses, and the study lasted for three years (2018-2020). Eviews 10.0 aided in the data analysis process, which involved the use of descriptive statistics and panel data regression. Stock prices in businesses in the Indonesian property and real estate sector were shown to be negatively affected by the Current Ratio (CR), positively affected by the Return on Assets (ROA), and unaffected by the Debt to Equity Ratio (DER).